Umbilical Cord Procalcitonin to Detect Early-Onset Sepsis in Newborns: A Promising Biomarker - Dongen, O. R. E.; van Leeuwen, L. M.; de Groot, P. K.; Vollebregt, K.; Schiering, I.; Wevers, B. A.; Euser, S. M.; van Houten, M. A. (Frontiers in Pediatrics, 2021)
Background: Up to 7% of neonates born in high-income countries receive antibiotics for suspected early-onset sepsis (EOS). Culture-proven neonatal sepsis has a prevalence of 0.2%, suggesting considerable overtreatment. We studied the diagnostic accuracy of umbilical cord blood and infant blood procalcitonin (PCT) in diagnosing EOS to improve antibiotic stewardship. Methods: Umbilical cord blood PCT was tested in newborns ≥ 32 weeks of gestation. Groups were defined as following: A) culture-proven or probable EOS (n=25); B) Possible EOS, based on risk factors for which antibiotics were administered for <72 hours (n=49); C) Risk factor(s) for EOS without need for antibiotic treatment (n=181); D) Healthy controls (n=74). Additionally, venous or capillary blood PCT and C-reactive protein (CRP) were tested if blood drawing was necessary for standard care. Results: Between June 2019 and March 2021, 329 newborns were included. Umbilical cord blood PCT was significantly higher in group A than in group C and D. No difference between venous or arterial samples was found. Sensitivity and specificity for cord blood procalcitonin were 83% and 62%, respectively (cut-off 0.1 ng/ml). Antepartum maternal antibiotic administration was associated with decreased PCT levels in both cord blood and infant blood directly postpartum in all groups combined. Conclusion: Umbilical cord blood PCT levels are increased in newborns ≥32 weeks with a proven or probable EOS and low in newborns with risk factors for infection, but PCT seems not a reliable marker after maternal antibiotic treatment. PCT could be useful to distinguish infected from healthy newborns with or without EOS risk factors.